Estimating the settling velocity of bioclastic sediment using common grain‐size analysis techniques. Issue 4 (29th December 2016) - Cuttler, Michael V. W.; Lowe, Ryan J.; Falter, James L.; Buscombe, Daniel
Abstract: Most techniques for estimating settling velocities of natural particles have been developed for siliciclastic sediments. Therefore, to understand how these techniques apply to bioclastic environments, measured settling velocities of bioclastic sedimentary deposits sampled from a nearshore fringing reef in Western Australia were compared with settling velocities calculated using results from several common grain‐size analysis techniques (sieve, laser diffraction and image analysis) and established models. The effects of sediment density and shape were also examined using a range of density values and three different models of settling velocity. Sediment density was found to have a significant effect on calculated settling velocity, causing a range in normalized root‐mean‐square error of up to 28%, depending upon settling velocity model and grain‐size method. Accounting for particle shape reduced errors in predicted settling velocity by 3% to 6% and removed any velocity‐dependent bias, which is particularly important for the fastest settling fractions. When shape was accounted for and measured density was used, normalized root‐mean‐square errors were 4%, 10% and 18% for laser diffraction, sieve and image analysis, respectively. The results of this study show that established models of settling velocity that account for particle shape can be used to estimate settling velocity of irregularly shaped, sand‐sized bioclastic sediments from sieve, laser diffraction, or image analysis‐derived measures of grain size with a limited amount of error. Collectively, these findings will allow for grain‐size data measured with different methods to be accurately converted to settling velocity for comparison. This will facilitate greater understanding of the hydraulic properties of bioclastic sediment which can help to increase our general knowledge of sediment dynamics in these environments.